Performance test on copper (II) removal by using fabricated thin layer composite: article - Yahya, Nur Yusrina; Kassim Shaari, Norin Zamiah (2016)
The fabrication of thin film composite (TFC) membrane by casting the hybrid membrane on the surface hydrophobic support membrane provides a remarkable improvement to the mechanical and thermal properties of the TFC membrane. Nowadays, the pollution of copper metal is a critical problem for environment due to its persistence and toxicity. This research paper outlines the use of TFC composite as a new technology for removal of copper ions from wastewater obtained from electroplating industry. As for analysis purpose, polymer blend of PVA/chitosan was used for copper ions removal as well. The industrial wastewater was characterized in term of biochemical oxygen demand (BOD), chemical oxygen demand (COD), turbidity, total suspended solid (TSS), pH value and concentration. The performance testing only focus on the effect of pH to the percentage removal and flux rate. Therefore, the pH was varied at 2.35 (without adjustment), 7 and 10. The result shows that the highest removal achieved at pH 7 for both composite. While, in term of flux rate, both composite was decreased with time by increasing the pH of feed solution. Due to hybrid membrane shows a consistent in removal, therefore the hybrid membrane is more preferred.